Elbow Community, Pottawatomie County - Beauchaine, Josh (Kansas State University, The Chapman Center for Rural Studies, 2010)
The Elbow Creek Community in Blue Township, Pottawatomie County, resided approximately five miles from Manhattan, Kansas near the border between Riley County and Pottawatomie County. Elbow was “settled” in the 1860's, and would officially die with the abandonment of the St. Patrick Church in 1928. The abandonment of St. Patrick's was not one of the reasons for its death, but it signified the end of the community.
Josh Beauchaine, “Elbow Community, Pottawatomie County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/15.
Keywords: Blue Township; Dempsey Family; Elbow; Irish Catholic; Pottawatomie County; St. Patricks Church